Perfil epidemiológico das doenças das glândulas salivares e reclassificação das neoplasias de acordo com a OMS/2005, em João Pessoa/PB - Agripino, Gustavo Gomes (2010)
This study aimed to determine the epidemiological profile of salivary glands diseases and perform the reclassification of the salivary glands tumors diagnosed within the period from 2003 to 2009, in the referral hospital to cancer diagnosis and treatment of João Pessoa city, Paraíba State, according to World Health Organization’s classification/2005. A retrospective study was performed, by review of 181 cases of patients with lesions in the major and minor salivary glands, including 104 men (57.1%) and 78 women (42.9%), mean age 49 years. The malignant epithelial tumors were more prevalent in the sixth and seventh decades of life (n = 14, 65.2%) and benign in the fourth decade (n = 12, 30.8%). Regarding the location, the parotid gland was the preferably located of benign epithelial tumors (n = 29, 74.4%), malignant epithelial neoplasms were preferentially distributed in the minor glands (n = 13, 60.9%). The most frequent benign tumor was pleomorphic adenoma (n = 31, 79.4%), followed by Warthin's tumor (n = 3, 7.7%) and myoepithelioma (n = 3, 7.7%). The most prevalent malignant neoplasms were: adenocarcinoma NOS (n = 6, 26.1%), adenoid cystic carcinoma (n = 5, 21.7%) and mucoepidermoid carcinoma (n = 4; 17.4). Among the cases reviewed, 56 were reclassified (30.9%), and the tumor that suffered the greatest number of reclassification was adenocarcinoma NOS (n = 13; 23.2%). The scores of coincidence among original and revised diagnosis was "great" within the benign epithelial tumors (Kappa = 0.867, p <0.05); "good" within the epithelial malignant neoplasms (kappa = 0.693, p <0.05); within the haematolynphoid tumors (Kappa = 0.797, p <0.05) and secondary tumors (Kappa = 0.451, p <0.05) those scores was considered as "moderate"; finally, the scores was "perfect" for soft tissue tumors (Kappa = 1, 00, p <0.05). We conclude that the salivary gland diseases present significant prevalence into the studied population, and pleomorphic adenoma was the most prevalent benign epithelial tumor and adenocarcinoma NOS the main malignant variant.